Comprehensive analysis of physiological and metabolomic responses to drought reveals specific modulation of acquired tolerance mechanisms in rice - Doddaraju, Pushpa; Dharmappa, Prathibha M.; Thiagarayaselvam, Aarthy; Vijayaraghavareddy, Preethi; Bheemanahalli, Raju; Basavaraddi, Priyanka A.; Malagondanahalli, Mohan Kumar V.; Kambalimath, Sumanth; Thulasiram, Hirekodathakallu V.; Sreeman, Sheshshayee M. (Physiologia Plantarum, 2023)
Mild stresses induce ``acquired tolerance traits'' (ATTs) that provide tolerance when stress becomes severe. Here, we identified the genetic variability in ATTs among a panel of rice germplasm accessions and demonstrated their relevance in protecting growth and productivity under water-limited conditions. Diverse approaches, including physiological screens, association mapping and metabolomics, were adopted and revealed 43 significant marker-trait associations. Nontargeted metabolomic profiling of contrasting genotypes revealed 26 ``tolerance-related-induced'' primary and secondary metabolites in the tolerant genotypes (AC-39000 and AC-39020) compared to the susceptible one (BPT-5204) under water-limited condition. Metabolites that help maintain cellular functions, especially Calvin cycle processes, significantly accumulated more in tolerant genotypes, which resulted in superior photosynthetic capacity and hence water use efficiency. Upregulation of the glutathione cycle intermediates explains the ROS homeostasis among the tolerant genotypes, maintaining spikelet fertility, and grain yield under stress. Bioinformatic dissection of a major effect quantitative trait locus on chromosome 8 revealed genes controlling metabolic pathways leading to the production of osmolites and antioxidants, such as GABA and raffinose. The study also led to the identification of specific trait donor genotypes that can be effectively used in translational crop improvement activities.